Association of High-Sensitivity C-Reactive Protein With Aneurysm Sac Shrinkage in Patients Undergoing Endovascular Abdominal Aneurysm Repair. (December 2022) - Kano, Masaki; Nishibe, Toshiya; Dardik, Alan; Iwahashi, Toru; Ogino, Hitoshi
Purpose: The factors associated with aneurysm sac shrinkage after endovascular aneurysm repair (EVAR) are not well established. As inflammation is implicated in aneurysm pathophysiology, we hypothesized that high-sensitivity C-reactive protein (hsCRP) was associated with aneurysm sac shrinkage after EVAR and compared the preoperative level of hsCRP between patients with and without postoperative aneurysm sac shrinkage after EVAR. Methods: From November 2013 to April 2019, 143 patients undergoing EVAR using Gore C3 Excluder (W. L. Gore & Associates, Inc, Flagstaff, Arizona) at our university hospital were included in this study. Aneurysm sac size was compared between that on baseline preoperative computed tomography (CT) and that on postoperative CT scans. A change in aneurysm sac size ≥5 mm was considered to be significant, whether due to enlargement or shrinkage. Results: Aneurysm sac size showed a significant decrease from 50.6 ± 9.8 mm to 47.1 ± 10.3 mm at 1 year. At 1 year postoperatively, aneurysm sac shrinkage (≥5 mm) was observed in 48 patients (34%), a stable aneurysm sac was noted in 93 patients (65%), and aneurysm sac enlargement was noted in 2 patients (1.4%). The mean preoperative hsCRP was 0.33 ± 0.54 mg/dL. Univariable analysis showed that preoperative hsCRP (p=0.029) and the presence of a renal cyst (p=0.002) were associated with aneurysm sac shrinkage. Multivariable analysis showed that preoperative hsCRP [>0.19mg/dL] (odds ratio [OR] = 0.22; 95% confidence interval [CI] = 0.05–0.96; p=0.042), and the presence of a renal cyst (OR = 0.31; 95% CI = 0.15–0.67; p=0.002) were independent risk factors for aneurysm sac shrinkage after EVAR. Conclusions: The level of preoperative hsCRP was independently associated with aneurysm sac shrinkage after EVAR in patients with abdominal aortic aneurysms. These data suggest that the high level of hsCRP can be a negative predictor for aneurysm sac shrinkage after EVAR.